Sistem Informasi Penjualan Grosir Familinta Berbasis Web - Tarigan, Santa Nova Elsa Liza; Hutapea, Marlyna Infryanty; Saragih, Rijois Iboy Erwin (Universitas Methodist Indonesia, 2024)
FAMILINTA wholesaler, which is located in Kaban jahe, Karo Regency of North Sumatra province, which provides a variety of cigarettes, and household goods, the process of selling goods is still written in the sales record book, in the process to find out and see the stock of available goods must also check one by one. So that it can make a sales management process slow, besides that several things are obstacles with the manual system, one of which is the large amount of data, thus making it complicated to process a sales data The author proposes, an information system to make an easy sales system, such as knowing the stock of available goods, Facilitating sales transactions, and making sales reports using the web, this system can make it easier for wholesale owners to present the amount of stock of goods, sales transactions and sales reports.